Impact of Pharmacist-Led Diabetes Self-Care Education on Patients With Type 2 Diabetes in Pakistan: A Randomized Controlled Trial - Allah Bukhsh; Allah Bukhsh; Tahir Mehmood Khan; Tahir Mehmood Khan; Pochamana Phisalprapa; Acharaporn Duangjai; Acharaporn Duangjai; Acharaporn Duangjai; Acharaporn Duangjai; Surasak Saokaew; Surasak Saokaew; Surasak Saokaew; et al. (Frontiers Media S.A., 2022)
Introduction: There is a little evidence on efficacy of pharmacy-based interventions on clinical outcomes of type 2 diabetes mellitus (T2DM) patients in Pakistan.Objective: To appraise the impact of pharmacist-led self-care education on glycemic control, self-care practices and disease knowledge of T2DM patients with poor glycemic control (HbA1c ≥ 7%).Methods: In this 6-months, randomized controlled trial (RCT), n = 75, T2DM patients seeking care at a diabetes clinic were randomized in to two groups. Intervention group (n = 38) received two face-to-face educational sessions (at enrollment and on week 12), whereas control group (n = 37) received usual care. Outcome measures such as glycemic control, self-care practices and disease knowledge were assessed at the time of enrollment and after 6-months in both groups.Results: Thirty-three intervention and thirty-three participants from the control group completed the study. Mean glycated hemoglobin (% HbA1c) significantly reduced in the intervention group from 9.00 ± 1.43 to 8.09 ± 1.16 (p < .01). However, no significant change was observed in the control group (9.20 ± 1.24 to 8.93 ± .97; p = .06). Cohen's d effect size of the intervention on HbA1c was .78. Percentage of participants achieving glycemic control (HbA1c < 7%) were significantly higher (p < .05) in the intervention group as compared to the control group (twenty-four vs. six), after 6 months of the trial. A significant (p < .01) improvement in mean scores for disease knowledge and self-care activities was also observed in the intervention group participants, whereas no significant improvements (p > .05) were observed in the control group.Conclusion: The study demonstrated an improvement in glycemic control, disease knowledge and self-care activities of T2DM patients who received pharmacist-led educational intervention. The study findings support clinical significance of integrating pharmacy-based interventions in diabetes management.